ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH MENDEPOSITKAN DANANYA MELALUI TABUNGAN BRITAMA JUNIO PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk. KANTOR CABANG TAMALANREA - Rosnaini Daga (AkMen JURNAL ILMIAH, 2016)
The purpose of this study was to menganalisisfaktor and the most dominant factor influencing customers to deposit funds through savings Junio BritAma at PT. Bank Rakyat Indonesia (Persero) Tbk Branch Tamalanrea. The analytical methods used are factor analysis and assisted by using SPSS to see tabulation score. The analysis showed that the factors that affect its customers to deposit funds through savings Junio BritAma at PT. Bank Rakyat Indonesia (Persero) Tbk Branch Tamalanrea are factors rate relationship with eigen value 2,941, the safety factor with eigen value 1,045 and factors features / savings facilities with eigen value of 1.011, while the factors yamhg most dominant is the interest rate by eigen value 2,941 ..